The Singer Sisters - Seltzer, Sarah (Flatiron Books, 2024)
"Two generations of a folk-rock dynasty collide over art, love, longing, and family secrets in this captivating and poignant debut. It's 1996, and alt-rocker Emma Cantor is on tour, with her sights trained on a record deal. Emma's got no lack of inspiration for her music - chiefly her mother Judie, a 1960s folk legend whose confessional songs made her an icon before her mysterious withdrawal from the public eye. Emma is baffled by Judie's coldness, and is deeply shaken when she learns a long-kept secret about their family. When Emma uncovers more about her mother's past, she is vaulted to new heights as a performer. But the knowledge she gains also propels her toward a musical betrayal that further fractures her relationship with Judie. Increasingly famous, but fragile and isolated, Emma grapples with her mother's legacy and what it means for her own future. With the richness of a beloved folk song, The Singer Sisters moves between '60s folk clubs and '90s music festivals, chronicling the ups and downs of stardom while asking what women artists must sacrifice for success."--